An ordeal that does not heal: understanding barriers to a cure for HIV-1 infection - Lichterfeld, Mathias; Gao, Ce; Yu, Xu G. (Trends in immunology, 2022)
With more than 38 million people living with HIV-1 (PLWH) worldwide, developing a cure for HIV-1 remains a major global health priority. Lifelong persistence of HIV-1 is frequently attributed to a pool of stable, transcriptionally silent HIV-1 proviruses, which are unaffected by currently available antiretroviral therapy (ART) or host immune activity. In this opinion article, we propose a more dynamic interpretation of HIV-1 reservoir cell biology and argue that HIV-1 proviruses frequently display residual viral transcriptional activity, making them vulnerable to longitudinal immune-mediated selection processes. Such mechanisms may, over extended periods of ART, induce an attenuated viral reservoir profile characterized by intact proviruses preferentially integrated into heterochromatin locations. We suggest that intensifying and accelerating naturally occurring selection mechanisms might represent a promising strategy for finding a potential cure for HIV-1 infection. HIV-1 reservoir cells persist lifelong, despite highly effective antiretroviral suppression treatment; we propose that these cells are under active immune selection pressure that might, during extended periods of antiretroviral therapy, eliminate a substantial number of proviruses and could ideally result in a reservoir profile dominated by intact proviruses integrated into heterochromatin positions. A considerable proportion of HIV-1 proviruses from people living with HIV-1 and treated with suppressive antiretroviral therapy is transcriptionally active and possibly vulnerable to antiviral immune recognition.HIV-1 reservoir CD4+ T cells may be subject to immune selection forces that can eliminate transcriptionally active intact proviruses; in contrast, intact HIV-1 proviruses integrated in heterochromatin positions appear to have a selection advantage and can persist long term.Some transcriptionally active proviruses might outcompete negative immune selection mechanisms through elevated rates of clonal proliferation or enhanced resistance to immune-mediated killing.An integration site profile dominated by intact proviruses integrated into heterochromatin positions may promote or enable a drug-free remission of HIV-1 infection.